PENGARUH LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK DAN PENGUNGKAPAN CSR SEBAGAI MODERASI - Magdalena Erlina (Jurnal Administrasi Bisnis, 2021)
This study aimed to analyze the effect of liquidity, profitability, firm size, independent commisioner toward tax aggressiveness and moderated by corporate social responsibility (CSR) disclosure in Indonesian mining companies listed on Indonesian Stock Exchange (IDX). This research used quantitative approach with descriptive and verification method. A sample of companies using purposive sampling technique and research data comes from financial reports, annual reports and annual reports of CSR disclosure of mining companies listed on the IDX and published in the period 2018-2019. Partial least square (PLS)-Structural Equation Model (SEM) was used as the method of analysis to examine the effect of the above variables supported by SmartPls 3.0 software system. The results shows that partially profitability affect significantly toward tax aggressiveness.  However, liquidity, firm size, and independent commissioner have no partial effect on tax aggressiveness. As for the moderating effect, the result also shows that CSR disclosure does not significantly affect to strengthen or weaken the correlation between liquidity, profitability, firm size and independent commissioner toward tax aggressiveness. Keywords: Liquidity, Profitability, Firm Size, Independent Commissioner, CSR Disclosure, Tax Aggressiveness